Correction to “Nonlinear Model Identification Method for Crane Damage Detection Without Baseline Data” - Bowei Li (IEEE Access, 2020)
Unfortunately, we did not consider transformation of the local coordinate system as we calculated the relative errors between the identified and the actual crack tips for each damage case. We made some mistakes in Table 8, Table 10, Figure 13 and Figure 22. In addition, some symbols were mistaken using in Equation 9 and Equation 38. They had no influence on the discussion and conclusions in the paper. The correct results are given here.